Memory in the Eyes. Reflections on Images and History: Can We Define a Colombian Repertoire? - Merlo, Alessandra; Universidad de los Andes (Pontificia Universidad Javeriana, 2016)
What is the relationship that images establishwith memory and history? In other words:What is the function pictures have in a particularnarration of past events and, specially,how can an image summarize this event andbe, almost, its mnemonic substitute? We wantto think of images, not only as a vehicle ofknowledge and historical memory, but also of a(non-neutral) constructor of an individual andcollective look. Finally, the text aims to ask ifColombians share a specific repertoire of imagesof their recent past and, if so, question whythose images, and not any other, have prevailed.In order to do this, we critically use theconcept of secular icon applied to an exercise carried out with a group of students.